You make me shine the making of a gay icon by the gay fandom of Regine Velasquez - Galang, Eric John Joaquin R. 1999
The recent increasing penetration and inclusion of gay audiences as agents in Philippine mass media subsequently welcome the viewing of Filipino celebrities through a queer lens, especially those who characteristically have amassed a gay following. Regine Velasquez is one of them, which all the more makes her a gay icon. As the study recognizes the queer developments in Philippine mass media and popular culture, it acknowledges their effects on audience reception. identity-building among audiences, fandom, stardom, and their respective academic disciplines. Furthermore, this study views the significance of the active participation of fans in the making of an icon. It is because of the intricate complexity of gay iconicity and identity that the research opted to examine the process by which a celebrity becomes a gay icon in the particular case of Regine Velasquez who, since the 90s and to this day, has made significant strides in the entertainment industry. In line with a qualitative research design, the study probed 10 gay fans of Regine Velasquez. The experiences of these fans are this study's units of analysis. Guided by theoretical developments to Laura Mulvey's male gaze, Jonathan Cohen's identification, and empirical studies about diva worship, with an overarching queer lens, this study will locate Regine Velasquez fans and how their identification, veneration, and productivities contribute to the gay iconicity of the Asia's Songbird.